Wypalenie zawodowe jako zagrożenie w pracy logopedy na oddziałach neurologii i rehabilitacji neurologicznej - Żulewska, Justyna; Pożoga, Karolina (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
A significant number of studies have been focused on the issue of occupational burnout among medical personnel, but none of the papers addresses this problem with respect to speech therapists. Speech therapists practicing a profession whose essence is working with people, providing help, exposure to the expectations of patients and their families, are exposed to the appearance of symptoms of occupational burnout. In addition, the nature and specificity of the speech therapist’s work in the departments of neurology and neurological rehabilitation can significantly affect the development of burnout syndrome. The aim of the study was to assess the degree of occupational burnout among speech therapists working in the departments of neurological rehabilitation and neurology, as well as to find out its causes. If the speech therapist is at risk of burnout, it is important to determine what the risk depends on and how to counteract it.